Perceived quality of life and physical activity in Brazilian older adults - Porto, Denilson Braga (2012)
The purpose of this study was to investigate the association between self-perceived quality of life and physical activity in Brazilian older adults. We investigated 199 individuals (117 men and 82 women) aged between 60 to 70 years old, employees of a public university. Physical activity was estimated by the short version of the International Physical Activity Questionnaire (IPAQ). Self-perceived quality of life was assessed using the World Health Organization Quality of Life (WHOQOL-Bref) questionnaire composed of four domains: physical, psychological, social relationship and environment. There was no difference in self-perceived quality of life between men and women. In contrast, quality of life was associated with physical activity even after adjustment for gender, schooling and income. The physical domain presented the strongest association with physical inactivity (Odds Ratio = 2.70, 95% CI 1.87-3.52). Only the environment domain evaluated by WHOQOL-Bref was not associated to physical inactivity. Among the older, improved self-perceived quality of life is positively associated to physical activity. © FTCD/FIP-MOC.